Butler in Action: The Base of Darlington Hall in Kazuo Ishiguro’s The Remains of the Day - Pokharel, Bishnu Prasad; Dangol, Bhabika (Kalika Journal of Multidisciplinary Studies, 2025)
This paper probes into the life of Stevens, a butler in Kazuo Ishiguro’s The Remains of the Day (1989), and explores the intricate social contrasts of post-war British society through his working-class experiences. This paper employs Raymond Williams’s theory of the Marxist base and superstructure to investigate the protagonist’s plight as a laborer in the sophisticated circle. This paper illustrates the prevailing economic and cultural dynamics of aristocratic society through a rigorous analysis of the reflective narrative of domestic help. It analyses Stevens as the working base and his high-profile employers as the superstructure embodying the societal, cultural, and political establishments. Scrutinizing Stevens’s unwavering professionalism and dignity in upholding the standards of Darlington Hall, this paper examines his butlering ideology as part of an unacknowledged English culture, reflecting the deep social pyramid. It uncovers how Butler’s significant role and his sacrifices in hosting international political meetings at Darlington Hall are implicitly labelled as a trivial task. As Stevens starts to change his professional philosophy, this paper explores his transformation from a workaholic to an individual with agency. Shedding light on the British social chasm through a base and superstructural framework, this paper reveals Butler’s unconscious longing to resist the dominant ideology. It argues that Stevens transcends his subservient role through his reminiscences, commitments, and gradual personal progression, ultimately confronting the remnants of his future.